PENGARUH LIKUIDITAS, PROFITABILITAS, LEVERAGE, CASH POSITION,DAN GROWTH TERHADAPKEBIJAKAN DEVIDEN - Sholikhah, Khurotun Amaliyah; Hermanto, Suwardi Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is meant to test the influence of liquidity, profitability, leverage, cash position, and growth tothe dividend policy of the infrastructure companies in 2008-20015 periods which are listed in Indonesia StockExchange (IDX).The sample selection has been conducted by using purposive sampling to the 118 financialstatementsof 53 go public infrastructure companies which are listed in Indonesia Stock Exchange(www.idx.co.id). The result of the research which has been done by using multiple analysis shows that liquidityand profitability give positive influence to the dividend policy, leverage and cash position give negative influenceto the dividend policy. Meanwhile, growth does not give any influence to the dividend policy with adjusted the RSquare is 0.623 or 62.3%.The independent variable give influence to the dividend payout ratio and theremaining is 0.377 or 37.7% has been influenced by other variables.Keywords : Liquidity, Profitability, Leverage, Cash Position, Growth and Dividen Policy.